RESPONSE OF TWO CULTIVARS OF OKRA FOR DIFFRENT MULCHES AND THEIR EFFECT ON GROWTH AND YIELD - & et al., Sadk (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
An experiment was conducted at the vegetable  field, Department of Horticulture and Landscape Gardening, Collage of Agriculture, University of Bagdad, to study the response of two cultivars of okra for different types of covering and their effect on growth, early and total yield. Two cultivars of okra ( Lahloba and Batra) were used, Two soil mulchs (with or without black mulch), and two tunnels cover (white and Agryl-17) were tested. This study was designed as a factorial (2*2*2) within RCBD with three replicates (24 experimental units).Results indicated: black soil mulch+ white cover treatment significantly increased the speed and percentage of germination, plant highest, leaves number, dry weight of the vegetative parts giving 14.7 and 15.16 days, 100 and 100%, 149.17 and 151.5 cm, 258.16 and 245.83 leaf.plant-1, 418.83 and 439.66 g.plant-1for both cultivars respectively. The same treatment gave the highest weight of the pods, number of pods, early and total yield 7.1 and 7.8 g., 27.35 and 22.86 pods.plant-1, 194.23 and 178.33 g.plant-1, 500.5 and 470.8 g.plant-1for both cultivars respectively compared to the lowest values achieved when the treatment without black mulch+ Agryl-17cover were used for both cultivars.